Development of a Solar-Powered Incubator for Poultry Eggs - Joseph Abutu; Mainigi Umar; James Wamayi Midala; Abdulkarim Muhammad Odeh; Garkuwa Haruna; Christian Ike; Sunday Albert Lawal (International Journal of Engineering Materials and Manufacture)
The development of solar-powered egg incubators holds promise for sustainable agriculture and poultry farming, particularly in areas with limited access to reliable electricity. Hence, in this work, locally sourced materials were used for the development of solar-powered incubator, with the aim of providing a sustainable and reliable alternative to traditional electricity-powered incubators. The design of the incubator was carried out using the different equations stipulated in literatures. Also, the performance of the incubator was investigated by determining the system temperature, relative humidity, percentage fertility and hatchability. The experimental results indicated that the total heat generated inside the incubator was 149,753.49 J, with contributions from air, eggs, water, and plywood. Also, there was consistent temperature and relative humidity readings throughout the incubation period with the temperature and relative humidity falling between 37.1-38.0°C and 50.6-56% respectively. The study also showed that the incubation process was conducted with diligence, leading to favorable outcomes (67% fertility and 75% hatchability) for embryo development and hatching success.